Preliminary screening of biomarkers in HAPE based on quasi-targeted metabolomics - Lin, Xue; Dai, Chongyang; Chen, Zhi; Zhang, Tongzuo; Pu, Xiaoyan (Frontiers in Physiology, 2023)
Acute mountain sickness (AMS) is a serious threat to the physical and mental health of people who quickly enter high plateaus. As a severe type of acute altitude sickness, high altitude pulmonary edema (HAPE) deserves more attention and in-depth research. In our study, through the detection of various physiological indexes and other phenotypes in a HAPE rat model, the HAPE group showed a significant decrease in oxygen partial pressure and oxygen saturation and a significant increase in pulmonary artery pressure and lung tissue water content. The lung histomorphology showed characteristics such as pulmonary interstitial thickening and inflammatory cell infiltration. We applied quasi-targeted metabolomics to compare and analyze the components of metabolites in arterial–veinous blood in control rats and HAPE rats. Using two machine algorithms and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, we speculate that D-mannose DOWN, oxidized glutathione DOWN, glutathione disulfide DOWN, and dehydrocholic acid DOWN in arterial blood play key roles in predicting the occurrence of HAPE; in venous blood, L-leucine DOWN, L-thyroxine DOWN, and cis-4-hydroxy-D-proline DOWN may have key roles, which can be considered biomarkers of HAPE. This result provides a new perspective for the further diagnosis and treatment of plateau disease and lays a strong foundation for further research.